Role of Lipid A Acylation in Yersinia enterocolitica Virulence - Pérez-Gutiérrez, Camino (American Society for Microbiology (ASM), 2010)
Yersinia enterocolitica is an important human pathogen. Y. enterocolitica must adapt to the host environment, and temperature is an important cue regulating the expression of most Yersinia virulence factors. Here, we report that Y. enterocolitica 8081 serotype O:8 synthesized tetra-acylated lipid A at 37°C but that hexa-acylated lipid A predominated at 21°C. By mass spectrometry and genetic methods, we have shown that the Y. enterocolitica msbB, htrB, and lpxP homologues encode the acyltransferases responsible for the addition of C(12), C(14) and C(16:1), respectively, to lipid A. The expression levels of the acyltransferases were temperature regulated. Levels of expression of msbB and lpxP were higher at 21°C than at 37°C, whereas the level of expression of htrB was higher at 37°C. At 21°C, an lpxP mutant was the strain most susceptible to polymyxin B, whereas at 37°C, an htrB mutant was the most susceptible. We present evidence that the lipid A acylation status affects the expression of Yersinia virulence factors. Thus, expression of flhDC, the flagellar master regulatory operon, was downregulated in msbB and lpxP mutants, with a concomitant decrease in motility. Expression of the phospholipase yplA was also downregulated in both mutants. inv expression was downregulated in msbB and htrB mutants, and consistent with this finding, invasion of HeLa cells was diminished. However, the expression of rovA, the positive regulator of inv, was not affected in the mutants. The levels of pYV-encoded virulence factors Yops and YadA in the acyltransferase mutants were not affected. Finally, we show that only the htrB mutant was attenuated in vivo.